EGR2 phosphatase regulates OST1 kinase activity and freezing tolerance in Arabidopsis. (14th November 2018) - Ding, Yanglin; Lv, Jian; Shi, Yiting; Gao, Junping; Hua, Jian; Song, Chunpeng; Gong, Zhizhong; Yang, Shuhua
Abstract: OST1 (open stomata 1) protein kinase plays a central role in regulating freezing tolerance in Arabidopsis ; however, the mechanism underlying cold activation of OST1 remains unknown. Here, we report that a plasma membrane‐localized clade‐E growth‐regulating 2 (EGR2) phosphatase interacts with OST1 and inhibits OST1 activity under normal conditions. EGR2 is N‐myristoylated by N‐myristoyltransferase NMT1 at 22°C, which is important for its interaction with OST1. Moreover, myristoylation of EGR2 is required for its function in plant freezing tolerance. Under cold stress, the interaction of EGR2 and NMT1 is attenuated, leading to the suppression of EGR2 myristoylation in plants. Plant newly synthesized unmyristoylated EGR2 has decreased binding ability to OST1 and also interferes with the EGR2‐OST1 interaction under cold stress. Consequently, the EGR2‐mediated inhibition of OST1 activity is released. Consistently, mutations of EGRs cause plant tolerance to freezing, whereas overexpression of EGR2 exhibits decreased freezing tolerance. This study thus unravels a molecular mechanism underlying cold activation of OST1 by membrane‐localized EGR2 and suggests that a myristoyl switch on EGR2 helps plants to adapt to cold stress. Synopsis: OST1 kinase, the master freezing tolerance regulator in Arabidopsis, is inhibited at warm temperatures by interaction with the membrane‐localized phosphatase EGR2. This interaction depends on EGR2 N‐myristoylation, attenuation of which upon cold stress provides a mean of activating OST1 at low temperatures. Plant type 2C protein phosphatase EGR2 is myristoylated by N‐myristoyltransferase NMT1. EGR2 interacts with and inhibits OST1 kinase activity. NMT1‐mediated myristoylation of EGR2 is important for its interaction with OST1. Cold stress attenuates EGR2 myristoylation and decreases its interaction with OST1, thereby activating OST1. Abstract : Attenuated myristoylation of PP2C family member EGR2 upon cold stress releases its inhibitory interaction with the master plant cold response factor OST1.